Ethical Diplomacy in a Globalized Era: Lessons from the Prophetic Model for Contemporary Sharia Economic Policy - Devaldo Eriyandes; Ramadika Panjinegoro; Sumarta; Farhan Farhan (Lentera Peradaban: Journal on Islamic Studies, 2025)
This research explores the reconstruction of Prophet Muhammad’s (PBUH) business diplomacy from an Islamic political economy perspective, serving as a response to the challenges of globalization, economic inequality, and ethical fragmentation in modern economic diplomacy practices. The study is motivated by the urgency of integrating prophetic values—such as trustworthiness (amanah), justice, transparency, and anti-monopoly—into a contemporary economic architecture that is often mired in materialistic orientations. Utilizing a library research method, this study analyzes approximately 20 primary and secondary sources, including sirah (biographies), Hadiths, Islamic political-economic literature, and international institutional reports. A thematic-historical-comparative approach was employed to examine the Prophet's diplomatic practices in Medina, compare them with modern economic diplomacy, and identify their relevance to the global halal industry and current public policy. The results indicate that the Prophet’s diplomacy emphasized market integrity, the protection of vulnerable groups, and social stability as the foundations of a sustainable economy. These prophetic values are proven compatible with modern governance principles; however, their implementation in Muslim-majority countries is still hindered by liberal market orientations, the commercialization of the halal industry, and policies that are not yet ethics-based. This study concludes that the prophetic business diplomacy model can serve as a strategic framework for developing Sharia economic policy, halal standardization, MSME empowerment, and international diplomacy. An integrative approach and policy innovation are required to ensure that prophetic values transition from moral discourse into operational foundations for modern economic governance.